2001
DOI: 10.1046/j.1526-0976.2001.005002082.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Treatment of Inflammatory Cytologic Abnormalities Detected By Papanicolaou Smears: A Pilot Study

Abstract: There is no statistically significant difference in the resolution of cytologic inflammatory changes among the study groups. Empiric metronidazole treatment has no benefit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…[30,32] Webb et al in 2001, however, found that there was no significant difference in the resolution of cytologic inflammatory changes after treatment with antibiotics. [33] Parashari et al in Maulana Azad Medical College, New Delhi, India in 1995 found that a large proportion of women with inflammatory smears had multiple gynecological infections and may be at risk of developing precancerous or cancerous changes. [34] They found 8 (72.7%) of 11 women who had dysplasia detected by colposcopy and confirmed by biopsy actually had inflammatory cytology in initial Pap smears.…”
Section: Discussionmentioning
confidence: 99%
“…[30,32] Webb et al in 2001, however, found that there was no significant difference in the resolution of cytologic inflammatory changes after treatment with antibiotics. [33] Parashari et al in Maulana Azad Medical College, New Delhi, India in 1995 found that a large proportion of women with inflammatory smears had multiple gynecological infections and may be at risk of developing precancerous or cancerous changes. [34] They found 8 (72.7%) of 11 women who had dysplasia detected by colposcopy and confirmed by biopsy actually had inflammatory cytology in initial Pap smears.…”
Section: Discussionmentioning
confidence: 99%